Antibody-mediated delivery of chimeric protein degraders which target estrogen receptor alpha (ERα) - Dragovich, Peter S.; Adhikari, Pragya; Blake, Robert A.; Blaquiere, Nicole; Chen, Jinhua; Cheng, Yun-Xing; den Besten, Willem; Han, Jinping; Hartman, Steven J.; He, Jintang; He, Mingtao; Rei Ingalla, Ellen; et al. (Bioorganic & medicinal chemistry letters, 2020)
[Display omitted] Chimeric molecules which effect intracellular degradation of target proteins via E3 ligase-mediated ubiquitination (e.g., PROTACs) are currently of high interest in medicinal chemistry. However, these entities are relatively large compounds that often possess molecular characteristics which may compromise oral bioavailability, solubility, and/or in vivo pharmacokinetic properties. Accordingly, we explored whether conjugation of chimeric degraders to monoclonal antibodies using technologies originally developed for cytotoxic payloads might provide alternate delivery options for these novel agents. In this report we describe the construction of several degrader-antibody conjugates comprised of two distinct ERα-targeting degrader entities and three independent ADC linker modalities. We subsequently demonstrate the antigen-dependent delivery to MCF7-neo/HER2 cells of the degrader payloads that are incorporated into these conjugates. We also provide evidence for efficient intracellular degrader release from one of the employed linkers. In addition, preliminary data are described which suggest that reasonably favorable in vivo stability properties are associated with the linkers utilized to construct the degrader conjugates.